Comparison of cytological evaluation using the cytobrush techniques and low volume lavage techniques in Colombian Creole mares diagnosed with endometritis - Gallego Rodríguez, Renso Sneider (2022)
The present study aimed to compare the endometrial cytological results obtained using the cytobrush and low volume lavage in Colombian Creole mares. In total, 90 mares with a clinical history of endometritis were used. The results of the cytological samples were compared under the variables of identification of the leukocyte reaction, type of leukocyte reaction, presentation of polymorphonuclear and mononuclear cells, presentation of bacteria, hyphae and cellular changes. A leukocyte reaction was found in 100% (90/90) of the cases with the cytobrush and in 93.9% (79/90) for the low volumen lavage (p=0.0031). The result of the presentation of polymorphonuclear cells was similar between the two techniques; however, the presence of mononuclear cells was more effective with the low-volume lavage technique. The finding of hyphae was 5.4% (6/90) with the cytobrush technique and 3.6 (4/90) with the low-volume lavage technique (p=0.515). There were no significant differences in the case of bacteria (p=0.2574). Cellular changes were found in 2.22% (4/90) of the samples with the cytobrush technique and none with the uterine lavage technique (p=0.0431).